(untitled) (Bulletin of Innovative Research, 2026)
This article analyzes the communicative functions of terminology used in English national sports games—golf, football, cricket, and tennis—from a linguistic perspective. The study examines the lexical-semantic features of sports terms, their functional load within professional discourse, and their pragmatic significance. Sports terminology is interpreted not only as a nominative linguistic unit but also as a means of information transmission, identification, evaluation, and the formation of social cohesion. The analysis identifies the contextual usage of terms, their metaphorical expansion, and their role in mass communication. As a result, English sports terminology is substantiated as functioning both as a national-cultural code and as a global communicative instrument.